2021
DOI: 10.3991/ijim.v15i17.23579
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Students’ Preferences in Online Algebra Instruction Pre- and Post-Covid-19

Abstract: This study is aimed towards understanding students’ preferences in online learning of College Algebra at a community college in the United States, before and after the Covid-19 pandemic. We analyze the results of Student Satisfaction surveys administered during Fall 19, Spring 20 and Fall 20 semesters. The classes were partially or fully online with synchronous and asynchronous components such as face-to-face and/or virtual meetings, pre-recorded video lessons, assignments through online homework platforms, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The findings of Akcay Ozkan & Budak [51] showed that using WBH reduces class time pressure to prioritize time for other activities while also limiting re-teaching what students already know to avoid subjective psychology. Furthermore, teachers can direct students to consolidate, deepen, and expand on what cannot be done in class due to time constraints.…”
Section: Web-based Homework (Online Homework)mentioning
confidence: 99%
“…The findings of Akcay Ozkan & Budak [51] showed that using WBH reduces class time pressure to prioritize time for other activities while also limiting re-teaching what students already know to avoid subjective psychology. Furthermore, teachers can direct students to consolidate, deepen, and expand on what cannot be done in class due to time constraints.…”
Section: Web-based Homework (Online Homework)mentioning
confidence: 99%